Effects of supportive treatment such as antioxidant or leukotriene receptor antagonist drugs on inflammatory and respiratory parameters in asthma patients - Tug, T.; Godekmerdan, A.; Sari, N.; Karatas, F.; Erdem, E. S. (Wiley, 2007)
In this study, prospectively, we aimed to determine the effects of the different treatment alternatives on the oxidant system and inflammatory and clinic determinants during the stable period of I month following an asthmatic attack. Thirty-one patients (22 female, nine male) were randomly divided into three groups following the stabilization of an acute asthma attack. The control group that is an additional group to the three patient groups consisted of 10 healthy volunteers (five female, five male). The following protocols were used for 4 weeks: Group 1: short-acting inhaler beta 2 mimetic as required (treatment A) + 800 mu g inhaler budesonide (treatment 13) + leukotriene receptor antagonist; Group II: treatment A and 13; Group III: treatment A and B +vitamin E. The serum levels before and after treatment of ecisinophilic cationic protein (ECP), leukotriene E-4 (LTE4), and malondialdehyde (MIDA) were determined. The values before and after treatment were statistically compared both with each other and control values. Pretreatment ECP, LTE4, and MDA levels for the three groups were significantly higher compared with post-treatment levels (P < 0.05 to P < 0.001) and the control levels (P < 0.01 to P < 0.001). However, when post-treatment levels were compared with those of the control group, no significant differences were found (P > 0.05). Lack of significant variation was observed when the pre- and post-treatment differences in the three groups were compared for each one of ECP, LTE4, and MDA levels (P > 0.05). Leukotriene receptor antagonist or antioxidant agents added to standard asthma treatment did not make a significant contribution on ECP, LTE4, and MDA levels and respiratory parameters such as spirometric function tests. Etiologic factors and/or the possible changes in different pathogenetic ways of the inflammation process may have been responsible for nonsignificant intertreatment difference in the biomarker levels. The result confirms that suppressing the inflammation in asthma enables the entire inflammatory pathologic process to be controlled.
Keywords: Eosinophil Cationic Protein; Oxidative Stress; Airway Inflammation; Bronchoalveolar Lavage; Plasma-Levels; Serum; Malondialdehyde; Marker; Copd; Ecp